A Complete Response of Orbital Metastases in Breast Cancer Patient Treated with Oral Chemotherapy: Case Report and Literature Review - Majd Mahmoud Sharaf; Yousef Maen Al-Oudat; Maher Saifo (Case Reports in Oncology, 2022)
Discrete extraocular muscles (EOMs) metastases are extremely rare events. Here is a case of isolated orbital metastases involving EOMs in a female patient who was previously diagnosed with triple-negative breast cancer. She received chemotherapy followed by radiotherapy. Years later, the patient complained of gradually progressive ptosis of the right eye that was associated with mild restriction of ocular movements. Magnetic resonance imaging showed a suspected metastatic lesion. An open biopsy was performed for pathological evaluation. Metastases from breast cancer were confirmed. Immunohistochemistry showed discordance of the estrogen and progesterone receptors. She received oral capecitabine (Xeloda®) and vinorelbine (NVB) followed by hormone therapy. At the time of reporting, our patient remained in remission for 28 months as from her initial diagnosis of orbital metastases.